2022
DOI: 10.1111/obr.13438
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of inequalities in the uptake of, adherence to, and effectiveness of behavioral weight management interventions in adults

Abstract: The extent to which behavioral weight management interventions affect health inequalities is uncertain, as is whether trials of these interventions directly consider inequalities. We conducted a systematic review, synthesizing evidence on how different aspects of inequality impact uptake, adherence, and effectiveness in trials of behavioral weight management interventions. We included (cluster-) randomized controlled trials of primary care-applicable behavioral weight management interventions in adults with ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 207 publications
(552 reference statements)
2
25
0
1
Order By: Relevance
“…As of now, men in Germany are not equally participating in public health offers and commercial programmes addressing WL. Thus, researchers and practitioners need to engage with suggestions to address more men, 39 attract more men, design and document programmes in regard to relative equity between genders 40 and have these programmes to promote effective WL. This study complements the research about men‐only interventions by adding info about possible predictors of WL in participants.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, men in Germany are not equally participating in public health offers and commercial programmes addressing WL. Thus, researchers and practitioners need to engage with suggestions to address more men, 39 attract more men, design and document programmes in regard to relative equity between genders 40 and have these programmes to promote effective WL. This study complements the research about men‐only interventions by adding info about possible predictors of WL in participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that socioeconomic factors have impacts on intervention/ trial uptake, intervention adherence and trial attrition. 63 Future research could consider using codesign principles to help better engage specific population groups, as well as GPs and PNs working with these groups, in the research design and development of the intervention. 64 CONCLUSION This trial of a multifaceted intervention designed to support better preventive care for overweight and obese patients from low socioeconomic areas in the real-world environment of Australian general practice showed some short-term improvement in health literacy and diet but did not show any change in weight or other physiological variables.…”
Section: Open Accessmentioning
confidence: 99%
“…Yet, other aspects needed to achieve long‐term health behavior change, such as uptake, followed by engagement, are reported less often in studies on mHealth interventions for physical activity 26 and other weight‐related behaviors. Whereas uptake is reported by the majority of studies, the information usually relates to sample size, and not to the representativeness of the sample, that is, the number of people who accepted the invitation to take part compared to all contacted persons 27 …”
Section: Introductionmentioning
confidence: 99%